(3WHbGJ GdeaSQjfs - (3GdOGhhOj , eMeO Hf Ydj Hf CMeO GdeGdcj, TeS GdOjf,J (B945 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI YeQ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B304s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B289 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B177 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1107s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs